ChemInform Abstract: Copper‐Catalyzed Intramolecular Dehydrogenative Amidation of Unactivated C(sp3)—H Bonds Using O2 as the Sole Oxidant. Issue 3 (29th December 2015) - Wang, Chunxia; Yang, Yudong; Qin, Dekun; He, Zhen; You, Jingsong
Abstract: The title process allows the synthesis of diverse β‐lactams.